The right of nonuse - Laitos, Jan. (Oxford : Oxford University Press, 2012)
This different perspective on the real causes of the ills plaguing the world's resources and environment re-examines the very nature of nature, and from this new perspective, argues that what is needed is for humans to grant to natural resources a legal right to be left alone - a right of nonuse.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Natural resources -- Law and legislation; Natural resources -- Government policy